POTENSI EKSTRAK GALAM SEBAGAI INSEKTISIDA NABATI TERHADAP HAMA KROP KUBIS (Crocidolomia pavonana) SKALA LABORATORIUM - S., Asikin,; Melhanah, Melhanah (AgriPeat, 2020)
In an effort to increase crop production often faced with pest attacks. Major losses resulting in crop failure can occur if the disturbance is not handled properly. The yield loss due to Crocidolomia pavonana cabbage crop pests is quite high reaching 80%. This pest is often found in every planting season of mustard plants. In addition, this pest is also spread quite widely in dry land and wetlands (tidal swamps and lowland swamps). Pests are generally controlled by chemical insecticides. Excessive use of chemical insecticides will have a negative impact on the environment such as resistance, and killing of natural enemies of pests. As an alternative, plant extracts can be used as natural insecticides in controlling this pest. The purpose of this study was to determine the effectiveness of galam extracts against pest cabbage plants C.pavonana. The study was conducted at the Laboratory of Pests Disease Research Institute for Swamp Farming Banjarbaru, South Kalimantan in March - September 2018. This study uses a completely randomized design with 3 treatments with plant extracts, 3 treatments without control, and 5 repetitions each. Each treatment uses 15 larvae of C. pavonana instar 2 on fresh mustard leaves. Botanical insecticide is formulated by dissolving solid extracts. The results showed that the use of galam extract can suppress cabbage crop pests with a mortality rate reaching 90.67%